2002
DOI: 10.1292/jvms.64.159
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Salmonella from Diarrheic Feces of Pigs.

Abstract: ABSTRACT. A survey of Salmonella was carried out in fecal samples of 887 pigs with diarrhea collected from 235 pig farms between April 1996 and March 2001. Salmonella was isolated from 84 feces (9.5%) of 887 pigs and from 45 (19.1%) of 235 farms. The higher prevalence was found in weaned pigs (12.4%) and fattening pigs (17.3%) than in sows (4.2%) and suckling pigs (4.5%). Isolation rates of S. Typhimurium were higher from weaned and fattening pigs than from the others. Therefore, risk of horizontal infection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…The isolation rates of Salmonella belonging to serovar O4 group were 68.1%, 58.7%, and 58.6% in the 1970s, 1980s and in 1998, respectively [7,17]. Furthermore, the isolation rates of Salmonella belong to serovar O4 group were 51.4% and 88.1% of pigs in disorder [1] or diarrhea [2], respectively. Thereby, our results in Experiment 2 may partially show the Salmonella prevalence of pigs in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The isolation rates of Salmonella belonging to serovar O4 group were 68.1%, 58.7%, and 58.6% in the 1970s, 1980s and in 1998, respectively [7,17]. Furthermore, the isolation rates of Salmonella belong to serovar O4 group were 51.4% and 88.1% of pigs in disorder [1] or diarrhea [2], respectively. Thereby, our results in Experiment 2 may partially show the Salmonella prevalence of pigs in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriological examination: Isolation of Salmonella was attempted from fecal samples as previously described [2,8].…”
Section: Serological Surveys On the Pig Farms (Experiments 2)mentioning
confidence: 99%
See 2 more Smart Citations
“…Many Salmonella serovars other than S. Choleraesuis cause food poisoning in human. Previous studies have shown that several serovars of Salmonella are prevalent among pigs [2,4,6,[11][12][13]. Hence, Salmonella prevalence among pigs causes a significant health problem for pigs and for people.…”
mentioning
confidence: 99%